Identification and characterization of virus-encoded circular RNAs in host cells. Issue 6 (22nd June 2022) - Chen, Shuting; Zheng, Jie; Zhang, Bingyue; Tang, Xinyue; Cun, Yewei; Wu, Tao; Xu, Yue; Ma, Ting; Cheng, Jingxin; Yu, Zuoren; Wang, Haiyun
Abstract : Emerging evidence has identified viral circular RNAs (circRNAs) in human cells infected by viruses, interfering with the immune system and inducing diseases including human cancer. However, the biogenesis and regulatory mechanisms of virus-encoded circRNAs in host cells remain unknown. In this study, we used the circRNA detection tool CIRI2 to systematically determine the virus-encoded circRNAs in virus-infected cancer cell lines and cancer patients, by analysing RNA-Seq datasets derived from RNase R-treated samples. Based on the thousands of viral circRNAs we identified, the biological characteristics and potential roles of viral circRNAs in regulating host cell function were determined. In addition, we developed a Viral-circRNA Database (http://www.hywanglab.cn/vcRNAdb/ ), which is open to all users to search, browse and download information on circRNAs encoded by viruses upon infection.